1995
DOI: 10.1210/endo.136.12.7588281
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor gene expression in the rat uterus during pregnancy and the estrous cycle and in response to gonadal steroid treatment.

Abstract: It is well established that uterine oxytocin receptors (OTRs) are strongly up-regulated immediately before parturition as well as in response to estrogen (E2) administration. Progesterone (P4), on the other hand, induces a rapid down-regulation. We recently cloned the rat OTR gene and characterized its expression in the rat uterus. In this study, we examined the regulation of OTR messenger RNA (mRNA) levels in rat uterus during pregnancy, the estrous cycle, and in response to gonadal steroid treatment. OTR mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
78
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 29 publications
10
78
1
4
Order By: Relevance
“…Paquin et al [2002] found that RA upregulated OT expression in the fetal heart, which is related to the OT-OT receptor system in P19 cell line. The OT gene promotor contains RA regulatory elements that respond to RA treatments in vivo and ex vivo in cultured cells [Richard and Zingg, 1991;Larcher et al, 1995]. These results suggest that OT is downstream of RA signaling during cardiac differentiation.…”
Section: Chemical Compounds and Othersmentioning
confidence: 88%
“…Paquin et al [2002] found that RA upregulated OT expression in the fetal heart, which is related to the OT-OT receptor system in P19 cell line. The OT gene promotor contains RA regulatory elements that respond to RA treatments in vivo and ex vivo in cultured cells [Richard and Zingg, 1991;Larcher et al, 1995]. These results suggest that OT is downstream of RA signaling during cardiac differentiation.…”
Section: Chemical Compounds and Othersmentioning
confidence: 88%
“…This increased uterine responsiveness to oxytocin occurs in parallel with an increase in the number of uterine oxytocin binding sites in rats [3,21], humans [4], rabbits [13,14] and cows [5]. Corresponding increases in uterine oxytocin receptor (OTR) mRNA expression in late pregnancy and parturition have been reported in rats [11,12,19], humans [9], cows [8] and sheep [24,25].Estrogen stimulates the number of uterine oxytocin binding sites [3,20,22] and OTR mRNA expression in ovariectomized (OVX) virgin rats [11,12]. However, injection of estrogen does not stimulate oxytocin receptor mRNA expression in late pregnant rats or progesterone-primed OVX virgin rats, but is effective only after ovariectomy and removal of progesterone, respectively [17].…”
mentioning
confidence: 88%
“…3). At the midpoint of PSP, the ERβ mRNA level was similar to that during estrus, indicating that the luteal phase did not affect the ERβ level as it did the ERα mRNA level.While OTR is expressed in the rat uterine myometrium [11], immunohistochemical and in situ hybridization studies have shown that ERα and ERβ expression occur in the Fig. 1.…”
mentioning
confidence: 99%
“…Nevertheless, it has been addressed in several species that a narrow relationship exists between estrogen (E), oxytocin (OT) and prostaglandins concentrations, especially towards the transition from pregnancy to parturition. In general, the concentration of uterine oxytocin receptors increases dramatically during gestation, under the influence of the rising estrogen levels (Larcher et al, 1995). Near term, oxytocin binds to its receptors in the decidua stimulating prostaglandin synthesis (Fuchs et al, 1983).…”
Section: Introductionmentioning
confidence: 99%